2015
DOI: 10.4238/2015.september.28.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed electromagnetic field therapy on the osteogenic and adipogenic differentiation of bone marrow mesenchymal stem cells

Abstract: ABSTRACT. We investigated the effects of pulsed electromagnetic fields (PEMFs) of 20 Hz/2 mT on the osteogenic and adipogenic differentiation of bone marrow stem cells (BMSCs). Sprague Dawley rat BMSCs were isolated and cultured in vitro. The BMSCs of the third passage were obtained and stimulated by PEMFs of 20 Hz/2 mT. The alkaline phosphatase (ALP) activity was measured according to the ALP assay kit manufacturer instructions, the BMSC osteogenic and adipogenic indicators were detected by semi-quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The work of Lu et al showed stimulatory effects of f = 20 Hz ELF-PEMF on ALP and Osteocalcin levels in rat-derived mesenchymal stem cells. In their experiments, ELF-PEMF exposure even suppressed adipogenic differentiation [79]. In line with this, both the study of Martino et al [80] and the study of Hannay et al [81] showed f = 15 Hz ELF-PEMF stimulatory effects on ALP activity (within few hours) and matrix mineralization (within 2-4 days) of SaOs-2 cells.…”
Section: Elf-pemf Effects On Bone Cell Functionmentioning
confidence: 64%
“…The work of Lu et al showed stimulatory effects of f = 20 Hz ELF-PEMF on ALP and Osteocalcin levels in rat-derived mesenchymal stem cells. In their experiments, ELF-PEMF exposure even suppressed adipogenic differentiation [79]. In line with this, both the study of Martino et al [80] and the study of Hannay et al [81] showed f = 15 Hz ELF-PEMF stimulatory effects on ALP activity (within few hours) and matrix mineralization (within 2-4 days) of SaOs-2 cells.…”
Section: Elf-pemf Effects On Bone Cell Functionmentioning
confidence: 64%
“…It is well known that differentiation of BMSCs is crucial to SONFH. A variety of physical, chemical or biological factors have been confirmed to affect the differentiation of BMSCs, such as pulsed electromagnetic fields [33], pravastatin [34], and miR-27a [35]. Furthermore, Runx2 is known to be essential in the process of osteogenic differentiation [36] and transdifferentiation [37] of BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…PTH increases intestinal calcium absorption and decreases efflux of calcium from bone as a calcium regulating hormone, and increases bone formation by promoting osteoblastogenesis and osteoblast survival as a natural anabolic agent [Esbrit and Alcaraz, ; Gardinier et al, ]. It was reported that an 8‐day Spacelab‐2 mission flight and long term bed rest caused a fall of PTH which was accompanied by decreased bone formation [Zerwekh et al, ; Lu et al, ]. In the current experiment, the serum PTH level of HLS + PEMFs group was kept at a similar level with the control, indicating that PEMFs may prevent bone loss by maintaining the systemic PTH level (Fig.…”
Section: Discussionmentioning
confidence: 51%